New media and the new Middle East - Seib, Philip M., 1949- (Palgrave Macmillan series in international political communication., 2007)
In one of the most politically volatile and dynamic regions of the world, new media technologies are profoundly influencing the course of events. Satellite television and the Internet are affecting how the people and states of the Middle East function individually and in a global context. In New Media and the New Middle East, topics ranging from women's rights to terrorism and countries from Israel to Saudi Arabia are examined in terms of how new media are reshaping lives and politics. Leading international scholars examine the global and regional ramifications of the proliferation of communication technologies and the information that they disseminate.